Stock Theft: Rural Livestock Farmers’ Entrepreneurial Perspectives - Mabunda, Mkateko Vivian; Maluleke, Witness; Barkhuizen, Jaco; Clack, Willie Johannes (International Journal of Criminology and Sociology, 2021)
The collation between stock theft and rural livestock farmers’ entrepreneurial perspectives receive limited attention in the field of Criminology and Criminal Justice, as well as ‘Business Administration’ nor entrepreneurial dominance industry. Conventionally, stock theft is nothing new in South Africa, traditional interpretations and recorded cases can be reportedly traced back to 1806. This study reflects the duality of stock theft, offering criminological [Theoretical] explanations and glimpses of attractive business enterprises by adopting the three elements of ‘Timmons Model of Entrepreneurial Process’ through the use of non-empirical research design: Systematic review, while featuring the most affected areas by stock theft in the Eastern Cape (EC), KwaZulu-Natal (KZN) and Mpumalanga (MP) Provinces respectively, while focusing on 2014-2020 financial years. This study establishes provides that this crime, instead of making more business avenues for rural livestock farmers, will continue to decrease the number of job opportunities. It is recommended that the South African government (I.e. national, provincial and local levels), agricultural industries, and the local South African Police Service Stock Theft Units (SAPS STUs) as a collective and commodity organisations will have to gravely consider offering adequate services required to bring workable solutions for initiation of entrepreneurial activities in the selected provinces.